Pet Attachment and Animal Abuse in Human Relationships with Pets as Inspiration for Digital Artworks - Ivana, Jessica; Pemayun, Tjokorda Udiana Nindhia; Mustika, I Ketut (Program Studi Seni Murni ISI Bali, 2024)
Humans and animals have coexisted for a long time with mutual benefits to one another. Relationships between species can create a balanced relationship for the survival of living things on earth. Attachment is an emotional relationship formed by individuals with other individuals who are considered stronger during their lives. Attachment will tend to encourage individuals to trigger closeness through contact and sad reactions due to separation. Individuals have the goal of seeking security and comfort in attachment. Human attachment to pets includes emotional, psychological, and physical interactions that will develop into a good mutual relationship. In attachment relationships, the role of empathy, attachment and anthropomorphism (the human tendency to assign characteristics, feelings and behaviors to non-human species) can influence the level of concern for pet welfare. Lack of empathy, attachment and anthropomorphism can lead to lower levels of care for animals, which may lead to neglect and abuse. Animal abuse is deliberate and repeated behavior with the aim of causing physical or psychological suffering to animals. Physical or psychological suffering in detail includes suffering and misery as well as the onset of pain and death of the animal.